Extended colostrum feeding and passive immunity in newborn calves - Baracat, Rosana Salles; Neto, Raul Machado; Daniele, Claudia; Bessi, Rosana; Packer, Irineu Umberto (Pesquisa Agropecuaria Brasileira, 1997)
The objective of this study was to evaluate the immunological condition of 32 Holstein newborn calves under different milk feeding programs. Animals with high and low condition of acquired passive immunity were splited in two groups, with and without extended colostrum feeding. The treatments were: T1 - high/milk; T2 - low/milk; T3 - high/colostrum; T4 - low/colostrum. Calves from T1 and T3 showed higher (p<0.0001) concentration of serum immunoglobulin (IgG) (33.46±7.0 mg/mL), when compared to T2 and T4 (21.46±6.1 mg/mL). The lowest concentration of serum IgG for T1 and T3 (high groups) were 22.53±4.0 mg/mL, higher (p<0.0001) than 15.19±4.7 mg/mL obtained for T2 and T4 (low groups). The dates when the lowest concentration occurred were also different (p<0.0604) after 50 days for T1 and T3 (high/milk and high/colostrum) and 40 days for T2 and T4 (low/milk and low/colostrum). The first occurrence of diarrhea was significantly different (p<0.03) between T2 and T3, 7 and 10.38 days respectively. The feeding of colostrum for extended period associated with good levels of passive immunity resulted in more protection against diarrhea compared to animals receiving only milk in the diet. The results also suggest a constant catabolism rate of immunoglobulin passively acquired.